One-year Prevalence, Comorbidities, and Cost of Hospitalizations for Alpha-1 Antitrypsin Deficiency among Patients with Chronic Obstructive Pulmonary Disease in the United States - Christopher M. Blanchette; Emily Zacherle; Joshua M. Noone; Bryce A. Van Doren; Debosree Roy; Reuben Howden (Journal of Health Economics and Outcomes Research)
**Objectives:** Little is known about severe chronic obstructive pulmonary disease (COPD) exacerbations among patients with Alpha-1 Antitrypsin Deficiency (AATD). We assessed inpatients with AATD and COPD among a sample of COPD inpatients to ascertain demographic, clinical and economic differences in the course of disease and treatment.